Crush implantation of a self-expanding interwoven stent over a subintimally recanalized standard stent in a TASC D lesion of the superficial femoral artery - Heilmeier, Britta; Strothmeyer, Anna-Maria; Cebola, Rita; Katus, Hugo; Blessing, Erwin (Vasa, 2012)
We demonstrate feasibility of implantation of a self-expanding interwoven nitinol stent in a claudicant, where recanalization attempt of a heavily calcified, occluded superficial femoral artery (TASC D lesion) was complicated by a previously implanted, fractured standard stent. Wire passage through the occlusion and beyond the fractured stent could only be achieved through the subintimal space. A dedicated reentry device was used to allow distal wire entry into the true lumen at the level of the popliteal artery. Despite crushing of the fractured stent with a series of increasingly sized standard balloons, a significant recoil remainded in the area of the crushed stent. To secure patency of the femoro-popliteal artery we therefore decided to implant the novel self-expanding interwoven nitinol stent (Supera Veritas (TM), IDEV), whose unique feature is an exceptional high radial strength. Patient presented asymptomatic without any impairment of his walking capacity at three month follow up and duplex ultrasound confirmed patency of the stent. Subintimal recanalizations can be complicated by previously implanted stents, in particular in the presence of stent fracture, where intraluminal wire passage often can not be achieved. Considering the high radial strength and fracture resistance, interwoven nitinol stents represent a good treatment option in those challenging cases and they can be used to crush standard nitinol and ballonexpandable stents.